De novo direct tandem duplication of the proximal long arm of chromosome 2: 46, XX, dir dup(2)(q11 X 2q14 X 2). Issue 1 (February 1984) - Mu, Y; Van Dyke, D L; Weiss, L; Olgac, S
Abstract : A child is described with a de novo direct duplication of the region 2q11 X 2 leads to 2q14 X 2. She probably represents the first reported case of proximal 2q duplication. The abnormalities included short stature, microcephaly, brachycephaly, depressed nasal bridge, prominent philtrum, congenital glaucoma, and mental retardation.